Alternative imaging strategy of solitary pulmonary nodule by FDG PET/CT: Can be imagined a tailored PET?. Issue 90 (May 2017) - Spadafora, Marco; Evangelista, Laura; Gridelli, Cesare; Cuocolo, Alberto
Abstract: Objective: Patients with solitary pulmonary nodule (SPN) are usually sent to total-body positron emission tomography/computed tomography (PET/CT) examination with 18F-fluorodeoxyglucose (FDG). However, a segmental scan strategy may improve cost/effectiveness in this category of patients. Conclusion: A segmental PET/CT scan only at the chest level could be performed in patients with indeterminate SPN. Limiting the PET/CT field to the thoracic region would greatly affect on radiobiology, department organization and health-care costs.